2001
DOI: 10.1063/1.1337080
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of ion implantation: Induced defects on substrate doping

Abstract: The characteristics of an ion implantation-induced defect in a silicon substrate are investigated. This defect is considered to be a complex of a point defect and a substrate dopant atom. The experiments are conducted by focusing on the dependence of the substrate dopant species (phosphorus and boron) on defect formation. The characteristics of the defect are investigated by measuring the bulk generation lifetime (τg) of metal–oxide–semiconductor capacitors, in which Si+ has been implanted to form the dopant-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Experiments measuring the bulk generation lifetime of MOS capacitors have shown residual ion implantation defects in the substrates remain in spite of annealing [19]. Phosphorus ion implantation not only results in the transition of the crystalline fullerenes to an amorphous material phase, but also produces a significant defect level, which is evident from solar cell efficiency ranges of only 10-20% [20].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Experiments measuring the bulk generation lifetime of MOS capacitors have shown residual ion implantation defects in the substrates remain in spite of annealing [19]. Phosphorus ion implantation not only results in the transition of the crystalline fullerenes to an amorphous material phase, but also produces a significant defect level, which is evident from solar cell efficiency ranges of only 10-20% [20].…”
Section: Introductionmentioning
confidence: 97%
“…Ion implantation induced defects in silicon substrates have been characterized to study the dependence of substrate dopant species (phosphorous and boron) on defect formations [29]. I-V characteristics of ion implanted solar cell devices at optical illumination have shown efficiencies as low as 0.01%.…”
Section: Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion implantation induced defects in a silicon substrate have been characterized by measuring the bulk generation lifetime of MOS capacitor and experiments have been conducted to study the dependence of substrate dopant species (phosphorous and boron) on defect formations [17]. I-V characteristics of ion implanted solar cell devices at optical illumination have shown the efficiency in the range of 0.01%.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of source-drain activation by low temperature annealing is a solid phase epitaxial regrowth (SPER) of the amorphous layer fabricated by the ion implantation. [5][6][7][8][9][10] Furthermore, the improvement of metal-oxide-semiconductor field-emission transistors (MOSFETs) current drivability without shrinking is also important in order to improve LSI performance. It has been shown that the current drivability of MOSFET is vastly improved by making the device on Si(110) surface.…”
Section: Introductionmentioning
confidence: 99%